The Future of Islamic Political Identity in Indonesia: Social Polarization, Money Politics, and Substantial Democratic Challenges - Khashogi, Luqman Rico; Widiasari, Eka (Postgraduate, State Islamic University Prof. K.H. Saifuddin Zuhri Purwokerto, 2025)
This study analyzes the diversity of Islamic political identity in Indonesia within the context of electoral political contestation, focusing on the influence of religious sentiment, money politics, and social polarization on the quality of democracy. A key factor in the weakening of substantive democracy is the growing complacency among Indonesia's younger generation, who, despite having formal voting rights and freedom of expression, are content with the declining quality of democracy. This study explores how complacency toward democracy interacts with Islamic political identity in elections, as well as the implications of social polarization, which has the potential to reduce social inclusion and diminish the quality of democracy. The research employs a literature study with a descriptive qualitative approach, examining various sources related to Islamic politics, religious populism, and the dynamics of democracy in Indonesia. The findings indicate that although Islamic politics remains strong in Indonesia, with religious identity serving as a stable factor across generations of support, money politics and religious populism are increasingly dominant, eroding the quality of democracy and fostering public distrust in the political system. The study concludes that, despite efforts to evolve Islamic politics in a more substantive and ethical direction, significant challenges related to exclusive polarization and political manipulation hinder the development of a more inclusive and equitable democracy. The research calls for reform in political governance and the electoral legislative framework to ensure a more substantial and higher-quality democracy in Indonesia, while mitigating the negative psychological impact on public political participation.